La cláusula del Estado Social y los derechos fundamentales sociales - Rodríguez-Arana Muñoz, Jaime (Universidad Nacional del Litoral, 2015)
The clause of the welfare state has been interpreted from a static, one-sided, single thought point of view. New and more human approaches are required, in line with the centrality and primacy of the principle of supreme dignity of human beings. In this respect, the study focuses on the concept of the fundamental rights of people in their social and individual versions, raising the issue as to the advisability of using the concept of solidary liberty.